Blood group relevance for the newborn - the ABO system and neonatal diseases - Izabela Cendal; Barbara Królak-Olejnik (Termedia Publishing House, 2023)
Blood group antigens, present on blood cells, can influence the susceptibility to or severity of various diseases. There are many studies describing such relationships in adults. However, in the case of newborns, there are only a few publications concerning the influence of blood type on diseases in the neonatal period. The present literature review deals with the influence of the ABO blood group system on the incidence and course of necrotizing enterocolitis and sepsis in the neonatal period. The review also concerns the effects of bleeding disorders and other changes in peripheral blood counts. Data presented on the relationship between blood group and the risk of developing or affecting the severity of the disease may be useful in neonatal practice, especially in the case of very small premature babies. There is a potentially faster, more accurate diagnosis, that will allow effective treatment of neonates.